2019
DOI: 10.1186/s13765-019-0459-8
|View full text |Cite
|
Sign up to set email alerts
|

Event-specific multiplex PCR method for four genetically modified cotton varieties, and its application

Abstract: Multiplex polymerase chain reaction (PCR) methods have been developed and validated for screening, tracing, and regulating genetically modified (GM) crops in quarantine and environmental monitoring. In this study, we aimed to develop a method to simultaneously detect four GM cotton varieties in order to establish a screening system for cotton volunteers. Based on the sequence of DNA in the junction between introduced gene and flanking genomic DNA of four GM cotton events, herbicide-tolerant MON88701 and DAS-81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Recently, numerous high-throughput DNA-based detection methods have been developed and applied. Among them, the multiplex PCR method, which amplifies multiple DNA targets in one reaction, is a simple strategy for monitoring and screening multiple GM plant samples (Jo et al 2016;Shin et al 2016;Eum et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, numerous high-throughput DNA-based detection methods have been developed and applied. Among them, the multiplex PCR method, which amplifies multiple DNA targets in one reaction, is a simple strategy for monitoring and screening multiple GM plant samples (Jo et al 2016;Shin et al 2016;Eum et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The validation of GMO detection methods is very complex and depends on the availability, type, and quality of the template DNA. The quantity and quality of genomic DNA from GMO monitoring samples were not sufficient for analysis; we therefore used LOD and random CRM mixture analysis to verify the efficiency of the multiplex PCR method (Eum et al 2019). The analysis of serially diluted CRM template DNA revealed that the PCR bands were detected at a DNA concentration of 25 ng/µl (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One oligonucleotide primer set for the adhC gene was used to confirm the stability of the PCR reactions. Specific PCR analysis using primer sets for 9 cotton events (T304-40, LLCOTTON25, MON1445, MON531, MON15985, MON88913, GHB614, GHB119, and 281-3006) was conducted to characterize the collected suspicious samples, as previously described (Table 1) [21][22][23][24]. The certified reference materials that served as controls in the PCR reactions were purchased from the American Oil Chemist's Society (AOSC; Urbana, IL, USA) and the Institute for Reference Materials and Measurements (IRMM; Geel, Belgium).…”
Section: Lmo Trait Identification and Event-specific Pcr Analysismentioning
confidence: 99%
“…Resistance to herbicides is the main characteristic of GMCs, and 47% of the world has planting areas of herbicide-resistant corn, soy, cotton, and canola. The usage of these products can significantly save on pesticides and herbicides, making the environment less contaminated (11). There are many reports from Iran (12), Serbia (13), and Italy (14) that GMOs are present in various foods.…”
Section: Introductionmentioning
confidence: 99%